1999
DOI: 10.1089/end.1999.13.591
|View full text |Cite
|
Sign up to set email alerts
|

Is Transurethral Vaporization a Remake of Transurethral Resection of the Prostate?

Abstract: The TUVP is a remake of TURP, with higher energy offering better results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Seventeen RCTs reported in 27 papers 55,57,128,129,138,140,142,156,158,162,193,[196][197][198][199][200][201][262][263][264][265][266][267][268][269][270][271] randomised a total of 1449 participants. …”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen RCTs reported in 27 papers 55,57,128,129,138,140,142,156,158,162,193,[196][197][198][199][200][201][262][263][264][265][266][267][268][269][270][271] randomised a total of 1449 participants. …”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A total of 14 studies 55,57,129,140,142,156,158,162,193,196,[198][199][200][201] reported duration of operation (Appendix 8.11 , Table 94). In half of the studies 55,57,129,158,162,199,200 this was longer in the TUVP group whereas in the other half 140,142,156,193,196,198,201 it was shorter in the TUVP group.…”
Section: Duration Of Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Kaplan et al, the mean duration of hospitalisation was 2.6±0.9 days in TUEVP versus 1.3±0.5 days in TURP cases. 9 In a study by Kupeli et al, the mean hospital stay in TURP cases was 4.5 days and in TUEVP cases the mean hospital stay was 2.5 days. 13 In TUEVP, about 85.7% had no complications, 2 patients (5.7%) had urinary tract infection which was treated by oral antibiotics, 1 patient (2.9%) complained of impotence who gradually improved over following 2 months without any intervention, 1 patient (2.9%) had retrograde ejaculation and did not improve even after 6 months of follow up and 1 patient (2.9%) had urethral stricture following UTI for which internal optical urethrotomy had to be done after 6 weeks.…”
Section: Discussionmentioning
confidence: 95%
“…2,6,7 It is a modification of the existing transurethral technology, is most recent promising alternative to TURP. 8,9 It is based on the principal of using electric current to vaporise and desiccate prostatic tissue. Vaporisation is done using high cutting current (up to 300 W) and desiccation is done using coagulation current (between 40 W and 70 W).…”
Section: Introductionmentioning
confidence: 99%